Matter exhibiting absolute rest and the origin of the solar system - Robertson, Daniel (International Journal of Advanced Astronomy, 2016)
The development of a volume of space containing matter which exhibits no movement of any kind is described. This is identified as matter in a state of Absolute Rest as envisaged by Newton. The proper-ties of matter in this state are described. The induction of the change from motion to rest and the re-verse are detailed and the latter applied to the origin of the Sun and the development of the Solar Sys-tem.